LOSS OF THE SELF IN POSTMODERN DISCOURSE. DECONSTRUCTING AND RECONSTRUCTING IDENTITY: - Soghomonyan, Amalya (Armenian Folia Anglistika, 2023)
The topic of the present article concerns the problem of deconstructing and reconstructing identity. In modernism we come across two contrary desires: the desire for a fixed identity and the desire to go beyond it. Under the concepts ‘the self’, ‘space’, ‘time’, ‘rationality’, ‘causality’, ‘society’, ‘history’ we not only mean the world, but also ourselves. The aim of the research is to study the alienated, absurd, existentialist anti-heroes which are all in the same position, failing to find the clear meaning of a personal, identifiable form of existence. In the postmodern age, the notion of a unique identity that used to command an aura has been lost due to the human ability to create exact reproductions. No one exactly knows what is meant by the term ‘postmodernism’. All that one knows is that it is some kind of a reaction against or an extension of modernism which ultimately turns on itself.